Manajemen Kepala Kantor Kementerian Agama Kota Jambi dalam Peningkatan Pelayanan Publik Bidang Pendidikan Agama Islam - Muhammad Kholis; Jalaluddin Jalaluddin (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
This study aims to examine the effort to improve public services in the field of Islamic education consists of curriculum and evaluation areas, educators and education personnel, facilities and infrastructure, student, institutional and information systems. This study uses qualitative descriptive methods through observation and indepth interviews with the Head of the Office of Religious Affairs Jambi City as key informant. Another informants are Head of Administration of sub-section, Section Head of the Madrasah Education, employees, and society. Furthermore, the technique of collecting data using interviews, observations and documentation study and data analysis. This research found that first, the Head Office of Religious Affairs Jambi City has a strategy to increase public services in the field of Islamic education, but the Head of the Office of Religious Affairs in Jambi City only involves some personnel clerks. Second, the implementation of public services in the field of Islamic education have not obtained good results, there are still dissatisfaction among Islamic teacher with the services provided by employees of Religious Office; Third, evaluation made by the Head Office of the Ministry of Religious Jambi in religious education public services have not been satisfactory, the gap between planning and implementation still happened in the field of Islamic education.